Multi-method findings on COVID-19 vaccine acceptability among urban refugee adolescents and youth in Kampala, Uganda. Issue 1 (2nd January 2023) - Logie, Carmen H.; Okumu, Moses; Berry, Isha; McAlpine, Alyssa; Musoke, Daniel Kibuuka; Hakiza, Robert; Perez-Brumer, Amaya; Baral, Stefan; Kyambadde, Peter
ABSTRACT : Scant studies have explored COVID-19 vaccine acceptability among refugees. However, contexts of forced migration may elevate COVID-19 vulnerabilities, and suboptimal refugee immunisation rates are reported for other vaccine-preventable diseases. We conducted a multi-methods study to describe COVID-19 vaccine acceptability among urban refugee youth in Kampala, Uganda. This study uses cross-sectional survey data from a cohort study with refugees aged 16–24 in Kampala to examine socio-demographic factors associated with vaccine acceptability. A purposively sampled cohort subset ( n = 24) participated in semi-structured in-depth individual interviews, as did key informants ( n = 6), to explore COVID-19 vaccine acceptance. Among 326 survey participants (mean age: 19.9; standard deviation 2.4; 50.0% cisgender women), vaccine acceptance was low (18.1% reported they were very likely to accept an effective COVID-19 vaccine). In multivariable models, vaccine acceptance likelihood was significantly associated with age and country of origin. Qualitative findings highlighted COVID-19 vaccine acceptability barriers and facilitators spanning social-ecological levels, including fear of side effects and mistrust (individual level), misinformed healthcare, community and family attitudes (community level), tailored COVID-19 services for refugees (organisational and practice setting), and political support for vaccines (policy environment). These data signal the urgent need to address social-ecological factors shaping COVID-19 vaccine acceptability among Kampala's young urban refugees. Trial registration: ClinicalTrials.gov identifier: NCT04631367 .